Portraying entanglement between molecular qubits with four-dimensional inelastic neutron scattering - E. Garlatti; T. Guidi; S. Ansbro; P. Santini; G. Amoretti; J. Ollivier; H. Mutka; G. Timco; I. J. Vitorica-Yrezabal; G. F. S. Whitehead; R. E. P. Winpenny; S. Carretta (Nature Communications, 2017)
Showing the presence of quantum entanglement in a system means it is beyond a classical description, but this is difficult to do experimentally. Here, the authors show how four-dimensional inelastic neutron scattering can quantify entanglement, demonstrating the method on a supramolecular dimer.